Benign Intracranial Hypertension -Is it Really Benign Always? - Ganger, Anita; Kumar, Narahari Kishore; Kumar, Praveen; Sabharwal, R K; Khosla, Amit; Saxena, Rohit (Nepalese Journal of Ophthalmology, 2018)
Background: In children, benign or idiopathic intracranial hypertension (IIH) is uncommon. The presenting symptoms are usually variable, which attribute to delay in diagnosis. Frequently encountered symptoms include; headache, vomiting, visual impairment, neck pain and diplopia. IIH in pre-pubertal children has distinct characteristics from the adult form. Delayed diagnosis in children usually attributes to the inability in picking subtle visual changes, which can subsequently leads to permanent visual damage. Objective: We report cases of two adolescent girls having IIH who presented with papilloedema, could be managed with lumboperitoneal shunting which resulted in favorable outcomes in terms of improved visual acuity and relief of symptoms. Case: We report two cases of IIH, presented with headache and severe visual loss, which showed non responsiveness to medical management and improved with a lumboperitoneal shunt procedure. Conclusion: In IIH cases, enhanced awareness, prompt diagnosis and treatment are important, to avoid the risk of permanent visual damage. Urgent surgical intervention is essential in patients who do not respond to medical treatment.